MODEL SISTEM BISNIS INTELIJEN DALAM PENGAMBILAN KEPUTUSAN PERSAINGAN TEKNOLOGI INFORMASI PERBANKAN - Rico Rizal Budidarmo; Marimin Marimin; Rina Oktaviani; Noer Azam Achsani (School of Business, Bogor Agricultural University (SB-IPB), 2010)
The objective of this study is to provide a structured modelling of business intelligence system for helping decision makers in banking IT management to extract external competitive information, to anticipate business environment changes, and to make appropriate and effective business decisions. Using a system perspective where the focus is on the interaction between dependent and independent variables, this study shows how IT management could use neural network to help improve the strategy formulation process. Combined with a business intelligence roadmap, the system has an ability to process internal and external data as well as providing intelligence analysis to determine IT strategy to anticipate competition. Expert system and artificial neural network were used in this competition submodel to predict bank’s transaction cost strategies which gives some priority actions for management to decide the best IT cost strategy such as focus, differentiation, and overall cost leadership.